Large-Conductance Calcium-Activated Potassium Channels in Glomerulus: From Cell Signal Integration to Disease - Tao, Jie; Lan, Zhen; Wang, Yunman; Hei, Hongya; Tian, Lulu; Pan, Wanma; Zhang, Xuemei; Peng, Wen (Frontiers in Physiology, 2016)
Large-conductance calcium-activated potassium (BK) channels are currently considered as vital players in a variety of renal physiological processes. In podocytes, BK channels become active in response to stimuli that increase local cytosolic Ca2+, possibly secondary to activation of slit diaphragm TRPC6 channels by chemical or mechanical stimuli. Insulin increases filtration barrier permeability through mobilization of BK channels. In mesangial cells, BK channels co-expressed with β1 subunits act as a major component of the counteractive response to contraction in order to regulate glomerular filtration. This review aims to highlight recent discoveries on the localization, physiological and pathological roles of BK channels in glomerulus.